Site Suitability Assessment for Shellfish Bottom Culture in Maitara Coastal Area - Tamrin; Taufiq Abdullah (Jurnal Ilmiah PLATAX, 2025)
Shellfish aquaculture has experienced significant growth in recent years. Several countries, including Indonesia, have successfully developed shellfish farming species. One area with potential for development is the coast of Maitara Island. This study aims to assess the land suitability for shellfish aquaculture development using the bottom culture method in Maitara Island. The research was conducted in the waters of Maitara Village. Observed parameters included substrate type, water depth, water temperature, salinity, DO, accessibility, and distance to settlements. The collected data were analyzed for water suitability, followed by visualization as a cultivation site map. The substrate type observations showed that the dominant substrate consisted of sand, gravel, and rocks. Water depth ranged from 2–22 meters, water temperature ranged from 29.40–28.70°C, salinity was 32 ppt, DO ranged from 3.25–3.70 mg/L, accessibility ranged from 0.07–0.52 km, and distance to settlements ranged from 0.02–0.63 km. Land suitability analysis indicated that the area is highly suitable for shellfish farming using the bottom culture method, with a total area of 24.8 hectares. The study concludes that the coastal area of Maitara Island is suitable for the development of shellfish farming using the bottom culture method. Keywords: Bottom culture, shellfish aquaculture, site suitability analysis, Maitara island.